Polystyrene as a vector of heavy metals in hard clam Meretrix lusoria under various salinities - Barus, Beta Susanto; Zhu, Zuhao; Cheuch, Chih-Yang; Chen, Kai; Wang, Jun; Cai, Minggang; Cheng, Sha-Yen; Wei, Huihua (Frontiers in Marine Science, 2023)
Microplastics and heavy metals are the two main contaminants that are often found in aquatic environments and can lead to major issues for aquatic organisms. Polystyrene (PS) is a type of microplastic that is commonly found in aquatic environments. Hard clams are one of the organisms that are often used as a bioindicator of water pollution, and they can live in a certain salinity range. The objective of this study is to investigate the potential of PS particles as heavy metal vectors in M. lusoria influenced by differences in salinity. The result showed that the highest increase in concentrations of all heavy metals in hard clams was found in those placed at higher salinities. Hard clams that were placed at higher salinity required more water, allowing more PS particles to enter the clams’ bodies. Hard clams placed at salinity 30‰ always gathered significantly more PS particles (p<0.05) than hard clams placed at the other two salinities (20 and 25‰). This is also corroborated by water depletion at a salinity of 30‰, which is significantly higher (p<0.05) than the other two salinities. Our findings indicate that PS particles have the potential as vectors for heavy metal pollutants in hard clams in environments of varying salinity.